2017
DOI: 10.1590/s0102-865020170100000004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of the effect of platelet rich plasma on the treatment of medial collateral ligament lesion in rabbits

Abstract: Purpose: To evaluate the use of platelet-rich plasma in the early stages of healing of traumatic injury of the medial collateral ligament in the knee of rabbits. Methods: Thirty rabbits were subjected to surgical lesion of the medial collateral ligament. Of these, 16 were treated with platelet-rich plasma and 14 with saline (control). After 3 and 6 weeks of treatment, 50% of the animals from each group were sacrificed, and biomechanical tests were performed on the injured ligament to compare the tensile streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Unfortunately, a limited number of manuscripts are available regarding the regeneration of ligaments 21 . A recent manuscript describes the regeneration of transected MCL from rabbits using platelet‐rich plasma (PRP) 22 . PRP significantly and progressively increased the tensile strength of the ligament in the treated group after 3 and 6 weeks as compared to saline.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a limited number of manuscripts are available regarding the regeneration of ligaments 21 . A recent manuscript describes the regeneration of transected MCL from rabbits using platelet‐rich plasma (PRP) 22 . PRP significantly and progressively increased the tensile strength of the ligament in the treated group after 3 and 6 weeks as compared to saline.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was the most used, using PRP in the treatment of medial ligament lesions in rabbits. Two centrifugations were done, the first one at 800 rpm for 8 minutes and the second, after supernatant removal, at 3200 rpm for 15 minutes 22 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The 31 in vivo ligament studies used various ligament models, including rat MCL, 2 canine ACL, 5,13,48,49,54,58,62,63 porcine ACL, 3,22,23,27,29,39,45 47 rabbit MCL, 14,26,31,40,66 rabbit ACL/CCL, 1,32,52,59,67 and human ACL (Appendix Table A3). 50,55,60 Among in vivo studies, detection and performance biases were consistently high, whereas selection, attrition, reporting, and other biases were consistently low (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…31 Other studies reported decreased inflammation in the PRP group compared with control groups. 1,14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation